2008
DOI: 10.37358/rc.08.6.1861
|View full text |Cite
|
Sign up to set email alerts
|

New Phenoxyacetic Acid Analogues with Antimicrobial Activity

Abstract: This paper presents experimental data regarding the synthesis and the antimicrobial activity of new 4-phenylazo-phenoxyacetic acids. All compounds were characterized by IR, UV-Vis, mass spectral data and by elemental analysis. These compounds were tested for their antibacterial activity against Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, Pseudomonas aeruginosa, Proteus vulgaris and for their antifungal activity against Candida albicans by disk diffusion method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The medicinal characteristics of azo‐synthetics were uncovered for a sulphonamide‐connected azo‐dye called Prontosil, which is employed as a medicine to treat microbic infections 33,34 . The azo‐synthetics' biological properties have garnered interest due to their potential as anti‐inflammatory, 35 antiviral (HIV), 36 anti‐oxidant, 37 anticancer, 38–40 bactericidal, 39–41 and fungicidal, 42–44 agents. The azo‐thiosemicarbazone ligand was created by combining the azo‐dyes moiety (‐N=N‐) with thiosemicarbazone that has a thionic moiety (‐C=N–NH–C(=S)–NH 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The medicinal characteristics of azo‐synthetics were uncovered for a sulphonamide‐connected azo‐dye called Prontosil, which is employed as a medicine to treat microbic infections 33,34 . The azo‐synthetics' biological properties have garnered interest due to their potential as anti‐inflammatory, 35 antiviral (HIV), 36 anti‐oxidant, 37 anticancer, 38–40 bactericidal, 39–41 and fungicidal, 42–44 agents. The azo‐thiosemicarbazone ligand was created by combining the azo‐dyes moiety (‐N=N‐) with thiosemicarbazone that has a thionic moiety (‐C=N–NH–C(=S)–NH 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting feature of azo compounds is their antimicrobial effects. 4-phenylazophenoxyacetic acids show antimicrobial activity against two gram-positive bacteria such as Staphylococcus ureus and Streptococcus pyegenes, which cause various diseases, and three gram-negative bacteria such as Pseudomonas aeruginosa, Proteus vulgaris and Esherichia coli [17,18]. It has been reported that some azo compounds with high antioxidant capacities act as Anti-Helicobacter pylori and Urease enzyme inhibitors by our research group [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Many glycerol derivatives such as fatty acid glycerides have been reported as bioactive against Gram positive, Gram negative, yeast and protozoa. Examples include monolaurin and monocaprin against Helicobacter pylori (Bergsson et al, 2002), E. coli (Kabara, 1978), Staphylococcus aureus, S. epidermidis, Streptococcus beta-hemolytic and alpha hemolytic, Corynebacterium, Giardia lamblia (Moanta and Radu, 2008) and Candida (Jarrahpour et al, 2004). Benzoic acid and benzoate ester derivatives are reported for their antibacterial (Friedman et al, 2003), antifungal (Terreaux et al, 2010), anti-inflammatory (Chen et al, 2007) and anti-protozoal (Kashif et al, 2017) activities.…”
Section: Introductionmentioning
confidence: 99%